Primary health care policy and vision for community pharmacy and pharmacists in Lebanon - Souheil Hallit; Carla Abou Selwan; Pascale Salameh (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Within a crippling economic context and a rapidly evolving healthcare system, pharmacists in Lebanon are striving to promote their role in primary care. Community pharmacists, although held in high esteem by the population, are not recognised as primary health care providers by concerned authorities. They are perceived as medication sellers. The role of the pharmacist in primary health care networks, established by the Ministry of Public Health (MOPH) to serve most vulnerable populations, is limited to medication delivery. The practice of the pharmacy profession in Lebanon has been regulated in 1950 by the Lebanese Pharmacists Association [Order of Pharmacists of Lebanon] (OPL). In 2016, the OPL published its mission, vision, and objectives, aiming to protect the pharmacists' rights by enforcing rules and procedures, raise the profession's level through continuous education, and ensure patients' appropriate access to medications and pharmacist's counseling for safe medication use. Since then, based on the identified challenges, the OPL has suggested several programs, inspired by the World Health Organization and the International Pharmaceutical Federation guidelines, as part of a strategic plan to develop the pharmacy profession and support patient safety. These programs included the application of principles of good governance, the provision of paid services, developing pharmacists' core and advanced competencies, generation of accreditation standards for both community pharmacy and pharmacy education, suggesting new laws and decrees, continuing education consolidation and professional development. There was an emphasis on all decisions to be evidence assessment-based. However, OPL faces a major internal political challenge: its governing body, which is reelected every three years, holds absolute powers in changing strategies for the three-year mandate, without program continuation beyond each mandate. Within this context, we recommend the implementation of a strategic plan to integrate pharmacy in primary health centers, promoting the public health aspect of the profession and taking into account of critical health issues and the changing demographics and epidemiological transition of the Lebanese population. Unless the proposed blueprint in this paper is adopted, the profession is unfortunately condemned to disappear in the current political, economic and health-related Lebanese context.